Loyalitas Konsumen Mie Gacoan Jatiwaringin Dipengaruhi Oleh Kualitas Produk Melalui Citra Merek - Putra, Yudha Wiratama; Silitonga, Eddy Sanusi (Jurnal Manajemen Bisnis Krisnadwipayana, 2026)
This study aims to analyze the influence of Product Quality on Consumer Loyalty of Mie Gacoan Jatiwaringin, as well as to test the role of Brand Image as a mediating variable in this relationship. This study used a quantitative approach with a survey method. The sample consisted of consumers who had previously purchased from Mie Gacoan Jatiwaringin, selected using a purposive sampling technique. The method was analyzed using Path Analysis. The results of the study indicate that: 1) Product quality has a positive and significant influence on consumer loyalty. 2) Product quality has a positive and significant influence on brand image. 3) Brand image has a positive and significant influence on consumer loyalty. 4) Brand image is proven to act as a mediating variable (possibly partial mediation), which means that product quality not only has a direct influence on loyalty, but also indirectly through the formation of a positive brand image in the minds of consumers.